Comparison of microRNA Expression Profile in Chronic Myeloid Leukemia Patients Newly Diagnosed and Treated by Allogeneic Hematopoietic Stem Cell Transplantation - Martins, Juliana Ravelli Baldassarre; Moraes, Leonardo Nazario de; Cury, Sarah Santiloni; Dadalto, Juliane; Capannacci, Juliana; Carvalho, Robson Francisco; Nogueira, Célia Regina; Hokama, Newton Key; Hokama, Paula de Oliveira Montandon (Frontiers in Oncology, 2020)
Chronic myeloid leukemia (CML) results from a translocation between chromosomes 9 and 22, which generates the Philadelphia chromosome, forming BCR/ABL1, an active tyrosine kinase protein that promotes cell growth and replication. Despite great progress in CML treatment such as with tyrosine kinase inhibitors, allogeneic-hematopoietic stem cell transplantation (allo-HSCT) is currently used as a curative treatment and is an important alternative for patients resistant to tyrosine kinase inhibitors. Studies have shown that unregulated expression of microRNAs which acts as oncogenes or tumor suppressors, is associated with human cancers and contributes to tumor formation and development by stimulating proliferation, angiogenesis, and invasion. Several authors have demonstrated the potential of microRNAs as biomarkers for cancer diagnosis, prognosis and therapeutic targets. In the present study, we compared the circulating microRNA expression profiles of 14 newly diagnosed patients with chronic phase-CML and 14 Philadelphia chromosome negative patients after allo-HSCT. We tested 758 microRNAs by reverse transcription quantitative polymerase chain reaction (RT-qPCR) array for each patient. The global expression profile of microRNAs revealed 16 upregulated miRNAs and 30 downregulated microRNAs. Ontological analysis suggested alterations in different ontological terms such as (1) biological process, (2) cellular process, (3) biological regulation, and (4) regulation of biological process. These results reveal the comprehensive microRNA profile of patients with CML in cytogenetic remission after allo-HSCT, providing new resources for exploring the disease and treatment strategies based on stem cell transplantation.